Pengaruh Model Pembelajaran PBL terhadap Kemempuan Berpikir Kritis Siswa pada Pembelajaran IPA - Desnita, Desnita; Dhalimunthe , Khairun Nisyah; Putri, Kurnia; Zahra, Novita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by the problems of students who are less able to solve problems. Most students are less able to respond and determine or get solutions to solve the problems they are facing. This study aims to analyze the effect of the Problem Based Learning model on learning science learning outcomes for class Vl SD Karya Bunda private school. This research using experimental research methods. There is a significant difference between the science communication skills of class V1 students who are taught using Audiovisual Media and the science learning outcomes of class V students without using Audiovisual media as evidenced by statistical data showing that the average scores of the two groups are at different averages. keywords: Problem Based Learning, Science, Audiovisual Media.